Sugar Transporter Proteins (STPs) in Gramineae Crops: Comparative Analysis, Phylogeny, Evolution, and Expression Profiling - Weilong Kong; Baoguang An; Yue Zhang; Jing Yang; Shuangmiao Li; Tong Sun; Yangsheng Li (Cells, 2019)
Sugar transporter proteins (STPs), such as H+/sugar symporters, play essential roles in plants’ sugar transport, growth, and development, and possess an important potential to enhance plants’ performance of multiple agronomic traits, especially crop yield and stress tolerance. However, the evolutionary dynamics of this important gene family in Gramineae crops are still not well-documented and functional differentiation of rice STP genes remain unclear. To address this gap, we conducted a comparative genomic study of STP genes in seven representative Gramineae crops, which are Brachypodium distachyon (Bd), Hordeum vulgare (Hv), Setaria italica (Si), Sorghum bicolor (Sb), Zea mays (Zm), Oryza rufipogon (Or), and Oryza sativa ssp. japonica (Os). In this case, a total of 177 STP genes were identified and grouped into four clades. Of four clades, the Clade I, Clade III, and Clade IV showed an observable number expansion compared to Clade II. Our results of identified duplication events and divergence time of duplicate gene pairs indicated that tandem, Whole genome duplication (WGD)/segmental duplication events play crucial roles in the STP gene family expansion of some Gramineae crops (expect for Hv) during a long-term evolutionary process. However, expansion mechanisms of the STP gene family among the tested species were different. Further selective force studies revealed that the STP gene family in Gramineae crops was under purifying selective forces and different clades and orthologous groups with different selective forces. Furthermore, expression analysis showed that rice STP genes play important roles not only in flower organs development but also under various abiotic stresses (cold, high-temperature, and submergence stresses), blast infection, and wounding. The current study highlighted the expansion and evolutionary patterns of the STP gene family in Gramineae genomes and provided some important messages for the future functional analysis of Gramineae crop STP genes.